Amorphous Calcium Phosphate and Amorphous Calcium Phosphate Carboxylate: Synthesis and Characterization - Indurkar, Abhishek; Choudhary, Rajan; Rubenis, Kristaps; Nimbalkar, Mansingraj; Sarakovskis, Anatolijs; Boccaccini, Aldo R.; Locs, Janis (American Chemical Society, 2023)
Amorphous calcium phosphate (ACP) is the first solid phase precipitated from a supersaturated calcium phosphate solution. Naturally, ACP is formed during the initial stages of biomineralization and stabilized by an organic compound. Carboxylic groups containing organic compounds are known to regulate the nucleation and crystallization of hydroxyapatite. Therefore, from a biomimetic point of view, the synthesis of carboxylate ions containing ACP (ACPC) is valuable. Usually, ACP is synthesized with fewer steps than ACPC. The precipitation reaction of ACP is rapid and influenced by pH, temperature, precursor concentration, stirring conditions, and reaction time. Due to phosphates triprotic nature, controlling pH in a multistep approach becomes tedious. Here, we developed a new ACP and ACPC synthesis approach and thoroughly characterized the obtained materials. Results from vibration spectroscopy, nuclear magnetic resonance (NMR), X-ray photoelectron spectroscopy (XPS), true density, specific surface area, and ion release studies have shown a difference in the physiochemical properties of the ACP and ACPC. Additionally, the effect of a carboxylic ion type on the physiochemical properties of ACPC was characterized. All of the ACPs and ACPCs were synthesized in sterile conditions, and in vitro analysis was performed using MC-3T3E1 cells, revealing the cytocompatibility of the synthesized ACPs and ACPCs, of which the ACPC synthesized with citrate showed the highest cell viability. © 2023 The Authors. Published by American Chemical Society --//-- https://pubs.acs.org/doi/10.1021/acsomega.3c00796. Published under the CC BY 4.0 licence.
The authors acknowledge financial support from the European Union’s Horizon 2020 Research and Innovation Program under grant agreement no. 857287 and Baltic Research Programme Project No. EEA-RESEARCH-85 “Waste-to-resource: eggshells as a source for next generation biomaterials for bone regeneration (EGGSHELL)” under the EEA Grant of Iceland, Liechtenstein and Norway No. EEZ/BPP/VIAA/2021/1. Institute of Solid State Physics, University of Latvia, received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART. 2
Keywords: Research Subject Categories::NATURAL SCIENCES